An investment of $27,000 was made by a business club.The investment was split into three parts and lasted for 1 year.The first part earned 8% interest,the second 6% and the third 9%.total interest from the investment was $2130.the interest from the first investment was three times the interest from the second find the amounts of the three parts of investments

Answers

Answer 1
Answer:

Answer

Find out the amounts of the three parts of investments .

To proof

let us assume that first part of investment be = u

let us assume that second part of investment be = v

let us assume that third part of investment be = w

As given

An investment of $27,000 was made by a business club.The investment was split into three parts and lasted for 1 year.

than the equation is written in the form

u + v + w = 27000

.The first part earned 8% interest,the second 6% and the third 9%.total interest from the investment was $2130.

8% is written in the decimal form

=(8)/(100)

= 0.08

6% is written in the decimal form

=(6)/(100)

= 0.06

9%  is written in the decimal form

=(9)/(100)

= 0.09

than the equation in the form

0.08u +0.06v +0.09w = 2130

equation written in the simple form

8u +6v +9w =213000

As given

the first investment was three times the interest from the second

u = 3v

Than the three equation in the form

u + v + w = 27000 , 8u +6v +9w =213000 , u = 3v

put this  u = 3v in the equation u + v + w = 27000 , 8u +6v +9w =213000

than the equation

30v +9w + 213000

4v +w = 27000

multiply the 4v +w = 27000 by 9 and subtracted with 30v +9w + 213000

36v-30v  +9w-9w =243000- 213000

6v = 30000

v =(30000)/(6)

v =$5000

put this in the equation

u =3v

u = 3× 5000

u= $15000

put the value u , v in the equation u + v + w = 27000

5000 + 15000 +w = 27000

w = $7000

than the three part be $5000, $15000,$7000

Hence proved




                         


Related Questions

of the vehicles on the road 1/2 are cars and 1/8 are motorcycles what fraction of the vehicles are not cars or motorcycles?
Solve the inequality.​ x+7≤11
Find the value of x in the isosceles triangle shown below.
Teach me about ratios
What is the difference?x2 + 3x+2 (x+2)(x+1)4X+2X-1X2+3x+2

Solve 2 cube root 8x+9=5

Answers

2 times the cube root of 8x+9=5
divide both sides by 2
cube root of 8x+9=2.5
cube everybody (put to 3rd power)
8x+9=2.5^3
8x+9=15.625
minus 9 both sides
8x=6.625
divie both sides by 8
x=0.828125

henry bought 1\4 pound of screws amd 2\5 pound of nails to build a skateboard ramp.what is the total weight of the screws and nails

Answers

1/4+2/5

13/20 is the answer.

Hope that helped :)

F(x) is a function? Please help

Answers

False because multiple inputs can’t have the same output

There are 1419 souvenir paperweights that need to be packed in boxes each box holds 15 paperweights how many boxes will be needed

Answers

Answer:

95

Step-by-step explanation:

1419 / 15 = 94.6

at 4:40 pm the thermometer outside of Yasmin's window read 40°c It had risen 8° betwen noon and 4:30 pm and 5° bertwen 7am and noon . What was the temperature at 7am?

Answers

at 4:30 the temperature is 40 degrees, and this temperature is 8 degrees more than what is was at noon. so we subtract 8 from 40 to get 32 degrees at noon. then we subtract 5 from 32 to get the temperature at 7 am. The temperature at 7 am is 27 degrees

An equation is shown below: 4(2x − 3) = 4 Part A: What is the solution to the equation above? Show your work using inverse operations. (5 points) Part B: Check using substitution to make sure your answer is correct. (5 points)

Answers

Answer:

The solution of the given equation is x = 2.

Step-by-step explanation:

The given linear equation is,

4(2x-3)=4

At first, we will eliminate '4' from the LHS by dividing both sides i.e., LHS and RHS by 4 because '4' is present in multiplication with the term containing unknown in LHS.

So, dividing both sides by '4', we get

(4(2x-3))/(4) = (4)/(4)

\implies 2x - 3 = 1

Our next step will be to eliminate '3' from the LHS that is being subtracted from the term containg unknown variable. For this, we will add '3' on both sides of the above obtained equation.

So, adding '3' on both sides, we get

2x - 3 + 3 = 1 + 3

\implies 2x = 4

Now, we will eliminate '2' from the LHS that is in multiplication with the unknown variable 'x'.

For this, we will divide both sides of the above obtained equation by '2'.

So, dividing both sides by '2', we get

(2x)/(2)=(4)/(2)

\implies x = 2

CHECKING :

For this, we will substitute x = 2 in the LHS of the given equation and then check whether it is equal to RHS or not.

LHS = 4(2x - 3)

= 4(2 × 2 - 3)

= 4(4 - 3)

= 4 × 1

= 4

= RHS

So, the solution of the given equation is x = 2.

Answer:

see explanation

Step-by-step explanation:

(A) Given

4(2x - 3) = 4 ( divide both sides by 4 )

2x - 3 = 1 ( add 3 to both sides )

2x = 4 ( divide both sides by 2 )

x = 2

(B)

As a check substitute x = 2 into the left side of the equation and if equal to the right side then it is the solution.

4(2(2) - 3) = 4(4 - 3) = 4(1) = 4 = right side

Hence x = 2 is the solution